Comparison of thromboelastography versus conventional coagulation tests in simulated Crotalus atrox envenomation using human blood. (February 2020) - Fortner, Grady A.; Devlin, John J.; McGowan, Andrew J.; Boboc, Michael; Natarajan, Ramesh; Zarow, Gregory J.
Abstract: Introduction: Pit viper bites are a source of significant morbidity and mortality. Pit viper bites can cause venom-induced consumptive coagulopathy (VICC), typically evaluated with laboratory-based conventional coagulation tests (CCTs). However, CCTs require a laboratory and average 1 h to conduct. Thromboelastography (TEG) provides real-time, point-of-care tests of coagulation that are fast and require no separate laboratory facilities, which could be advantageous in both hospital and austere settings. However, the relative efficacy of TEG versus CCTs was unclear, particularly at low venom concentrations. Therefore, the objectives of this study were to test human blood with various concentrations of pit viper venom using CCTs and TEG to determine dose-dependent changes, lowest observed effect concentration (LOEC), and sensitivity to detecting samples out of normal diagnostic range. Methods: Blood samples from 20 volunteers were mixed with varying concentrations of western diamond back rattlesnake ( Crotalus atrox ) venom based on the mouse LD50IV (none, 0.5%, 1%, 2%, 33%, 66%, and 100% LD50IV ). Samples were split and assessed with both CCTs including prothrombin time (PT), international normalized ratio (INR), partial thromboplastin time (PTT), fibrinogen, and D-dimer, along with TEG measures of reaction time (R), kinetic time (K), rate of clot formation (α-angle), and clot strength (MA). Data were analyzed as dose-dependent concentration-based changes in raw values and in percent of samples exceeding diagnostic thresholds using ANOVA and nonparametric statistics at the p < .05 threshold. Results: All evaluations showed significant concentration-dependent changes, and 100% of samples exceeded diagnostic thresholds at 33%LD50IV and above, save D-dimer. At 0.5%LD50IV, R, K, α-angle, PT, and INR were significantly different from controls, and at 1%LD50IV, mean values exceeded diagnostic thresholds for R, K, α-angle, MA, PT, and INR, but not for PTT, D-dimer, or fibrinogen. At 2%LD50IV, 100% of samples were out of normal range for K, α-angle, and PT. Conclusion: TEG is effective in coagulopathy evaluations of in vitro simulated pit viper envenomation. At low venom concentrations, TEG performed as well or better than the majority of CCTs. These findings provide empirical evidence supporting the use of TEG to rapidly and accurately evaluate VICC. Highlights: In vitro C. atrox venom coagulotoxic effects were concentration dependent. At ≥33%LD50IV, PT/INR, PTT, fibrinogen, and TEG measures R, K, MA, and α-angle had high sensitivity. At 2%LD50IV, K, MA, α-angle, and PT/INR showed high sensitivity. R showed moderate sensitivity, but PTT and fibrinogen showed low sensitivity at 2%LD50IV . D-dimer showed no significant difference versus control at any tested venom concentration.